The Gene for Ribosomal Protein L13, rplM, Is Located Near argR, at About 70 Minutes on the Escherichia coli Chromosomal Linkage Map - Dabbs, Eric R. (1982)
Mutants of Escherichia coli with alterations in the electrophoretic mobility of ribosomal protein L13 were used to locate rplM, the gene for this protein, on the chromosomal linkage map. rplM was situated between gltB and argR, at about 70 min.